Steven Ehrlich architects : multicultural modernism - Ehrlich, Steven, 1946-; Steven Ehrlich Architects; Palm Springs Art Museum (Mulgrave, Victoria, Australia : Images Publishing, 2006)
Includes bibliographical references (p. 268)